2016
DOI: 10.3280/ecag2016-002004
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level labelling: too complex for consumers?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Past research has already stressed the importance of providing specific knowledge about eco‐labels besides general environmental knowledge (Taufique, Siwar, Chamhuri, & Sarah, ) and in the packaging context, Magnier and Crié () have pointed out that logos can only be fully understood in combination with more detailed verbal information. We think that a multilevel label as suggested by Weinrich et al () would help to provide differentiated information while keeping complexity for consumers low, since past research has pointed out the problems of over‐burdening the consumer with too complex labels (Olander & Thogersen, ). However, using an eco‐label can also have negative effects for companies, as consumers’ perception of product efficacy may suffer, since at least, a part of the population tends to believe that green products and packaging exhibit a lower performance regarding other criteria (Weinrich & Spiller, ; Wood et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has already stressed the importance of providing specific knowledge about eco‐labels besides general environmental knowledge (Taufique, Siwar, Chamhuri, & Sarah, ) and in the packaging context, Magnier and Crié () have pointed out that logos can only be fully understood in combination with more detailed verbal information. We think that a multilevel label as suggested by Weinrich et al () would help to provide differentiated information while keeping complexity for consumers low, since past research has pointed out the problems of over‐burdening the consumer with too complex labels (Olander & Thogersen, ). However, using an eco‐label can also have negative effects for companies, as consumers’ perception of product efficacy may suffer, since at least, a part of the population tends to believe that green products and packaging exhibit a lower performance regarding other criteria (Weinrich & Spiller, ; Wood et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable purchasing choices are highly complex decisions (Moisander, ) causing ‘information overload’ (Weinrich & Spiller, ); however, the typical mode of thinking available for making everyday decisions does not support the cognitive effort that complex decision‐making calls for (Biel & Dahlstrand, ). So it is not surprising that research has identified both time pressure and cognitive overload together with a lack of willingness to process more information (Weinrich, Franz, & Spiller, ; Weinrich & Spiller, ) as factors limiting consumer selection of environmentally friendly packaging (Biel & Dahlstrand, ; Sheth, Newman, & Gross, ). In past studies, consumers have also expressed concern about their ability to judge packaging solutions (Lindh, Olsson, & Williams, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%